The Degree Of Control Of Diabetes And Cardiovascular Risk Factors For Patients Visiting Tishreen Hospital In Lattakia - Gehgah, Akram; Salman, Ruba; kanna, Kenana (Latakia University Journal -Medical Sciences Series, 2020)
Background: Diabetes mellitus (DM) is considered an independent cardiovascular risk factor. Having in mind concomitant occurrence of diabetes and other cardiovascular risk factors, it is expected that patients with poor glucoregulation will have more cardiovascular risk factors and higher cardiovascular risk than patients with good glucoregulation. Aim : To compare cardiovascular risk and cardiovascular risk factors between patients with poorly controlled and patients with well-controlled Diabetes mellitus. Materials and Methods :This was a prospective , descriptive study conducted at internal medicine department at Tishreen University Hospital , Lattakia , Syria during the period between 2018 – 2019 . 120 patients aged ≥ 40 years suffering from Diabetes mellitus type 2 were included . Patients with glycosylated hemoglobin (HbA1c) > 7% were considered to have poorly controlled diabetes. The following data and parameters were monitored: age, sex, family history, data on smoking and alcohol consumption, BMI (body mass index), blood pressure, fasting blood glucose, total cholesterol, triglycerides, LDL, and HDL . For the assessment of cardiovascular risk, the WHO / ISH (World Health Organization/ International Society of hypertension) tables of the 10-year risk were used. Results : 46.7% of DM patients had poorly controlled DM . Differences in the mean values of systolic, diastolic blood pressure, duration of diabetes , fasting glucose, total cholesterol, LDL cholesterol are statistically significant higher in patients with poorly controlled diabetes. Hypertension more frequently occurred in patients with poorly controlled DM. The majority of patients with well-controlled DM (71.8%)belong to the group of low and medium cardiovascular risk, while the majority of patients with poorly controlled DM (62.5%) belong to the group of high and very high cardiovascular risk. In our research, there was a significant difference in cardiovascular risk in relation to the degree of DM regulation, and HbA1c proved to be an important indicator for the emergence of the CVD. Conclusion : There are significant differences in certain risk factors between patients with poorly controlled and well controlled DM. Patients with poorly controlled diabetes mellitus have a higher cardiovascular risk than patients with well controlled diabetes. The value of HbA1c should be considered when assessing cardiovascular risk. الخلفية : يعتبر الداء السكري (DM) عامل خطرٍ قلبي وعائي مستقلٍ. مع الأخذ في الاعتبار الحدوث المتزامن للداء السكري و عوامل الخطر القلبية الوعائية الأخرى ، من المتوقع أن يملك المرضى مع ضبط سيء لسكر الدم عوامل خطر قلبية وعائية و خطراً قلبياً وعائياً أعلى من المرضى مع ضبط جيد لسكر الدم . الهدف : مقارنة المخاطر القلبية الوعائية و عوامل الخطر القلبية الوعائية بين المرضى مع ضبط سيء للداء السكري و المرضى مع ضبط جيد للداء السكري . المواد و الطرق : أجريت هذه الدراسة الاستهلالية الوصفية في قسم الأمراض الداخلية العامة في مشفى تشرين الجامعي , اللاذقية , سوريا في الفترة ما بين 2018 – 2019 . شملت الدراسة 120 مريض بتشخيص داء سكري نمط ثاني بعمر ≥ 40 سنة . تمّ اعتبار المرضى مع خضاب غلوكوزي < 7% مرضى ذوي ضبط سيء للداء السكري . تم رصد البيانات التالية : العمر ، الجنس ، القصة العائلة ، بيانات عن التدخين و استهلاك الكحول ، مشعر كتلة الجسم (BMI) ، ضغط الدم ، سكر الدم الصيامي ، الكولسترول الكلي ، الشحوم الثلاثية ، LDL ، و HDL . لتقييم الخطر القلبي الوعائي ، تم استخدام جدول منظمة الصحة العالمية / الجمعية الدولية لارتفاع التوتر الشرياني) للخطر خلال 10 سنوات . النتائج : كان 46.7% من المرضى ذوي ضبط سيء للسكري . كانت الفروق في متوسط قيم الضغط الشرياني الانقباضي ، الضغط الشرياني الانبساطي , مدّة الإصابة بالداء السكري , سكر الدم الصيامي ، الكوليسترول الكلي ، الكوليسترول LDL أعلى بشكل هام إحصائياً لدى مرضى الضبط السيء. لوحظ حدوث ارتفاع التوتر الشرياني بشكلٍ أكبر لدى مرضى الداء السكري مع ضبط سيء. غالبية مرضى الداء السكري جيد الضبط (71.8%) هم ضمن فئة الخطر المتوسط و المنخفض , في حين أنّ غالبية مرضى الداء السكري سيء الضبط (62.5%) هم ضمن فئة الخطر المرتفع و المرتفع جداً. في بحثنا ، كان هناك فرق هام في المخاطر القلبية الوعائية وفقاً لدرجة ضبط السكري ، و أثبت الخضاب الغلوكوزي (HbA1c) أنه مؤشر هام لخطر الأمراض القلبية الوعائية . الخلاصة : هناك فروق ذات دلالة إحصائية في بعض عوامل الخطر بين المرضى مع ضبط سيء و المرضى مع ضبط جيد للداء السكري. يملك المرضى مع ضبط سيء للداء السكري خطراً قلبياً وعائياً أكبر من المرضى مع ضبط جيد للسكري. يجب أن تؤخذ قيمة HbA1c في الاعتبار عند تقييم الخطر القلبي الوعائي .